Analisis Penataan Penumpukan Kontainer Terhadap Lahan Depo di PT. Mentari Sejati Perkasa Surabaya - Daryanto, Anggi Gita; Hardjono (Universitas Hang Tuah, 2018)
PT. Mentari Sejati Perkasa is a company engaged in the field of sea transportation services, namely container service, container depot, shipping agent, stevadoring. The importance of container depots is very influential because it is a container or place for stacking empty containers or container contents. The right and neat container arrangement in the depo area is very influential on the limited depo land area. Because if the container arrangement is not neat, the activities taking place in the depot area will not run smoothly. The tidier in the preparation and arrangement of containers will make optimal activities that occur in the depo area and can also make time efficient in loading and unloading activities that occur in the depo area, distribution of containers from the depot to the port or vice versa.